2015
DOI: 10.14423/smj.0000000000000255
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Differences in HIV Viral Loads and Progression to AIDS among New HIV Cases

Abstract: The reasons behind differences in proportions of rural and urban residents who were diagnosed as having AIDS or progressed to AIDS despite similar initial CD4(+) T-cell counts and VL suppression at 1 year are unclear and should be explored in future studies. Future prevention and treatment efforts may need to consider the unique characteristics of rural populations in the South.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 1 publication
1
32
0
Order By: Relevance
“…; Weissman et al. ). Rural residents are more likely be hospitalized for ambulatory care–sensitive conditions, be diagnosed at a later cancer stage, and experience worse outcomes for chronic kidney disease (Spoont et al.…”
Section: Discussionmentioning
confidence: 98%
“…; Weissman et al. ). Rural residents are more likely be hospitalized for ambulatory care–sensitive conditions, be diagnosed at a later cancer stage, and experience worse outcomes for chronic kidney disease (Spoont et al.…”
Section: Discussionmentioning
confidence: 98%
“…One study of the US veteran population identified a positive association between rural-small town/remote residence and high ART adherence during the year after ART initiation, and another study of a nonurban population showed no difference at diagnosis but significantly more rapid progression to AIDS in the nonurban group. 10 , 70 Even within the same state, however, findings conflict. In contrast to the findings of no difference in virologic suppression at one year, another study in SC in which statewide viral load values from 2005 to 2012 were analyzed found that mean viral load decreases were significantly affected by urban versus nonurban residence with urban residents having better viral load decreases.…”
Section: The Hiv Continuum Of Care In the Nonurban Contextmentioning
confidence: 98%
“…The heaviest burden of domestic HIV infection, morbidity, and mortality lies in the American South . Although early diagnosis and continuity of treatment are essential to the overall well‐being and survival of Persons Living with HIV (PLWH), delayed diagnosis, deferred HIV care linkage, and attrition to treatment are prominent issues in the South . Nonmetropolitan (rural and suburban) areas are of particular concern, as these regions have the most rapid growth of HIV infection rates and AIDS‐related deaths .…”
mentioning
confidence: 99%